Application of cryogenic detectors in time-of-flight mass spectrometry of large biomolecules; Proceedings of Symposium Measurement at the Quantum Limit, DPG 2005, Berlin, 4-9 March, 2005 - Uchaykin (Uchaikin) S. V. Sergey Victorovich; Christ P.; Rutzinger S.; Seidel W.; Proebst F. (2005, 2005)
В фонде НТБ ТПУ отсутствует